Sovereign ratings of Ukraine: factors and risks - Borzenko, E.A. (KSU Publ., 2020)
Object: The aim of the article is to develop theoretical principles that reveal the content , functions and role of sovereign credit ratings in the financial market, justify the transformation of methodological approaches to determining sovereign ratings in times of crisis, and develop recommendations regarding the regulation of rating agencies in Ukraine. Methods: The methodological basis of the article was the provisions of general economic theory, a systematic approach, a trend-based forecasting method, analytical alignment methods, and a statistical method. Findings: As a result of the study , it was found that if a country is assigned a speculative level rating, most of the capital flows into short-term speculative operations. High riskiness, micro and macroeconomic uncertainty, and limited opportunities for the state to influence the economic environment and processes in the country and market participants create an ideal environment for speculative capital movement. Conclusions: A certain flow of fuse I capi t ala of the real sector in spe kulyativny sector - due to growing risks and the cost of capital is the use of modern tools of business and making financial and economic decisions. Reduce the risks of investors and improve the investment attractiveness are designed such innovative systems and those hnologii as the financial cont ling , value-orientations annoe management, financial co m munikatsii, modern methods of assessment ki credit risks , and the like. Them practical advice in complex e with makroe to nomic reforms in the country will help to improve the ratings of our state as a whole and individual economic entities, create favorable conditions for the inflow of capital into the real economy.
Украинаның егеменді рейтингтері: факторлар мен қауіптер
Суверенные рейтинги Украины: факторы и риски
Keywords: sovereign ratings; corporate sector of the economy; credit and investment ratings; speculative ratings; capital